Integrative Methods in Teaching and Learning History in Malaysia - Seman, Ahmad Ali; Yaakop, Mohd Rizal; Nurdin, Iing (International Journal of Asian Social Science, 2019)
The objective of this study is to examine the effectiveness of Integrative Teaching Methods in teaching and learning History. Interviews and observation were implemented to review the student's perspective on integrative methods. The effectiveness of Integrative methods is reviewed from the perspective of students. The study found that students’ response was very positive. They are happy and keen to involve in activities organized through multiple sources and methods. In addition, respondents show appreciation on integration of various races, especially when they respond to the question on the Implementation of Integrative Value (INI) and Highlighting the Talent and Potential Students (MPB), because these methods highlight the elements of unity that can be seen from a clear and practical class demonstrations. Furthermore, findings from the observation reveal that MPB method makes students more active, interested, having equal opportunity, creating good learning environment and establishing an appreciation to national values. Similar reaction is also found in the application of UKP. The implication of this study is that the use of Integrative Methods could transformed the way to teach and to learn History, making it more interesting, intriguing and encouraging as well as creating a student- oriented learning. In future, this may facilitate the element of unity and national integration to be incorporated into every students’ curriculum.